Internet-based Distributed Collaborative Engineering Analysis - Qiuli Sun; Kurt Gramoll (Concurrent Engineering, 2002)
This paper proposes an engineering analysis environment that allows remote users to conduct three-dimensional finite element analysis collaboratively through the Internet. Java and Java 3D were chosen to develop the working prototype due to their advantages of platform-independence and network supporting. The environment allows remote users to work collaboratively on the same analysis object simultaneously. It reads the geometric data generated by the collaborative geometric modeling environment. The user can interact directly with the geometric model to perform operations, such as applying, editing, and deleting boundary conditions and forces. The operations are propagated among the team members, which creates a distributed shared environment. The commands are transmitted instead of the generated data, and thus the network traffic associated with the collaboration is minimized. Different from classical server/client models,# the environment adopts a strategy in which the client-side application has full analysis capabilities while the server only manages communication. The essential features for distributed collaboration are discussed. The actual design consideration of the working prototype is presented to help illustrate the complexity and development of the collaborative environment. The environment is open to the public at www.vcity.ou.edu.
Keywords: internet-based; collaborative; engineering analysis; distributed; finite element; remote